Digital Economy Challenges and Opportunities in Malawi - Chitragar, Suresh L. (Journal of Global Economy, Business and Finance, 2025)
This study provides a comprehensive analysis of the challenges and opportunities associated with the Digital Economy DE in Malawi, focusing on the Information Communication Technology ICT sector. The research highlights the potential of DE to foster innovation, but also underscores the limitations imposed by inadequate digital infrastructure and loss of information control. The study employs a qualitative approach, guided by the New Public Management NPM model, and includes interviews with senior public officers from various departments. The findings reveal that while DE offers numerous benefits to Malawi, these advantages are often overshadowed by the prevailing challenges. The study concludes with a call for the Government of Malawi and key stakeholders to devise strategies to mitigate these challenges, thereby maximizing the benefits of DE. The insights gleaned from this research contribute to the knowledge base required for effective DE implementation in Malawi.